Laminate and method for manufacturing laminate
A laminate with a hydrophilic resin and thermoplastic styrene elastomer and hydrocarbon wax combination addresses the issue of maintaining oxygen barrier properties under high humidity and after bending, providing enhanced flexibility and resistance.
Patent Information
- Application Number
- JP2024020788
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-02-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-02-15
AI Technical Summary
Existing laminates for packaging materials face challenges in maintaining oxygen barrier properties under high humidity conditions and after bending, as hydrophilic resins like polyvinyl alcohol swell, reducing barrier effectiveness, and thermosetting resins like styrene-butadiene rubber lack flexibility and water vapor barrier performance.
A laminate structure comprising a base material, a first barrier layer with a hydrophilic resin, and a second barrier layer with a thermoplastic styrene elastomer and hydrocarbon wax, which together form a flexible and tough coating film that maintains oxygen and water vapor barrier properties under high humidity and after bending.
The laminate achieves excellent oxygen barrier properties and blocking resistance under high humidity conditions and after bending, with improved flexibility and reduced swelling of the hydrophilic resin, enhancing overall performance.
Smart Images

Figure 2025000542000001 
Figure 2025000542000002 
Figure 2025000542000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a method for producing the laminate. [Background technology]
[0002] Conventionally, aluminum foil and aluminum-deposited plastic films and papers have been widely used for materials that require oxygen barrier properties, such as food packaging materials. However, in recent years, due to environmental issues and other factors, there has been a strong demand for packaging materials to be thinner, have simpler lamination methods, and be more recyclable, and so there has been a growing movement away from aluminum.
[0003] In addition, thermoplastic resin films in which a PVDC (polyvinylidene chloride) layer is formed on a plastic film by coating exhibit high oxygen barrier properties not only under low humidity but also under high humidity conditions, and also have high barrier properties against water vapor. However, when this PVDC-coated thermoplastic resin film is incinerated during waste disposal, chlorine gas and dioxins are generated due to the chlorine in the PVDC, which may have a significant adverse effect on the environment and human body, so there is a demand for a shift to other materials.
[0004] As a chlorine-free gas barrier material, a coated film in which polyvinyl alcohol or an ethylene-vinyl alcohol copolymer is coated on a thermoplastic resin film is well known. Patent Document 1 describes a laminate having a structure of a substrate / anchor coat layer / barrier layer, in which the barrier layer contains a polyvinyl alcohol resin and an ethylene-maleic anhydride resin. Patent Document 2 describes a laminate having a structure of a substrate / anchor coat layer / barrier layer, in which the barrier layer contains a polyvinyl alcohol resin. However, the high hydrogen bond resin that exerts gas barrier properties by hydrogen bonds with hydroxyl groups such as polyvinyl alcohol resin as the gas barrier layer as in Patent Documents 1 and 2 has a problem that the resin swells under high humidity, weakening the hydrogen bond property and causing a rapid decrease in barrier properties. The laminate described in Patent Document 3 uses a polyvinyl alcohol resin for the gas barrier layer, and uses a coating agent using styrene-butadiene rubber, which is a thermosetting resin, to suppress the decrease in barrier properties under high humidity. However, the flexibility of the coating film of styrene-butadiene rubber is low, and there is a concern that there is a problem with the water vapor barrier performance, and there is a concern that the polyvinyl alcohol resin swells under high humidity, reducing the oxygen barrier property, and there is also a concern that the coating film breaks when folded, reducing the oxygen barrier property. Patent Document 4 describes a laminate having a polyvinyl alcohol layer, a layer containing a silicic acid condensate and a tabular pigment, and a layer formed by a styrene-butadiene latex coating agent. Since latex is a colloidal water dispersion of rubber, it is classified as a thermosetting resin. The target laminate has a layer containing a silicic acid condensate and a tabular pigment, and a layer formed by a styrene-butadiene latex coating agent, and the coating film does not have the flexibility to be used for soft packaging, so there is a concern that the coating film breaks when folded, reducing the oxygen barrier property. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-144761 A [Patent Document 2] Patent Publication No. 2021-194822 [Patent Document 3] Patent Publication No. 2021-54897 [Patent Document 4] JP 2003-211578 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a laminate that is excellent in oxygen barrier properties under high humidity conditions and after bending, and in blocking resistance. Effect of the Invention
[0007] As a result of extensive research into the above problems, the inventors have found that the above problems can be solved by using the laminate described below, and have thus completed the present invention.
[0008] That is, the present invention relates to the following [1] to
[10] .
[0009] [1] A laminate having a substrate, a first barrier layer, and a second barrier layer, the first barrier layer comprises a hydrophilic resin, The laminate, wherein the second barrier layer comprises a thermoplastic styrene elastomer and a hydrocarbon-based wax.
[0010] [2] The laminate according to [1], wherein the thermoplastic styrene elastomer is a styrene-based block copolymer.
[0011] [3] The laminate according to [1] or [2], wherein the styrene-based block copolymer is at least one selected from the group consisting of styrene-isoprene-styrene block copolymer (SIS), styrene-isobutylene-styrene block copolymer (SIBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butylene-styrene block copolymer (SBS), styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-isoprene-styrene block copolymer (SBIS), hydrogenated styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-butadiene block copolymer (SB), and acid-modified, acid anhydride-modified, and amine-modified products thereof.
[0012] [4] The laminate according to any one of [1] to [3], wherein the mass ratio of the thermoplastic styrene elastomer to the hydrocarbon wax in the second barrier layer is 95:5 to 30:70.
[0013] [5] The laminate according to any one of [1] to [4], wherein the first barrier layer further contains an inorganic layered filler.
[0014] [6] The laminate according to [5], wherein the inorganic layered filler is at least one selected from the group consisting of montmorillonite, mica, and kaolin.
[0015] [7] The laminate according to any one of [1] to [6], wherein the second barrier layer further contains an extender pigment.
[0016] [8] The laminate according to any one of [1] to [7], wherein the substrate is a plastic substrate or a paper substrate.
[0017] [9] The laminate according to any one of [1] to [8], further comprising an anchor coat layer.
[0018]
[10] The laminate according to any one of [1] to [9], further comprising a sealant.
[0019]
[11] A method for producing a laminate having a substrate, a first barrier layer, and a second barrier layer, comprising the steps of: A step of applying a first barrier coating agent to form a first barrier layer; applying a second barrier coating agent to form a second barrier layer; the first barrier coating agent contains a hydrophilic resin, The method for producing a laminate, wherein the second barrier coating agent comprises a thermoplastic styrene elastomer and a hydrocarbon wax.
[0020] According to the present invention, it is possible to provide a laminate that is excellent in oxygen barrier properties under high humidity conditions and after bending, as well as in blocking resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The following describes in detail the embodiments of the present invention. However, the described embodiments and explanations of the requirements are merely examples of the embodiments of the present invention, and the present invention is not limited to these contents as long as they do not depart from the gist of the present invention.
[0022] [Laminate] The laminate of the present invention is a laminate having a substrate, a first barrier layer, and a second barrier layer, the first barrier layer containing a hydrophilic resin, and the second barrier layer containing a thermoplastic styrene elastomer and a hydrocarbon wax. The laminate preferably further has an anchor coat layer, and is preferably used as a packaging material.
[0023] In the laminate of the present invention, the first barrier layer has oxygen barrier properties, and the second barrier layer has water vapor barrier properties. The hydrophilic resin contained in the first barrier layer swells under high humidity conditions by incorporating water molecules between the molecular chains of the hydrophilic resin, resulting in a decrease in oxygen barrier properties. On the other hand, in the second barrier layer, the thermoplastic styrene elastomer and the hydrocarbon wax are appropriately compatible with each other, so that a flexible and tough coating film can be formed, and a water vapor transmission rate that is significantly lower than when each resin is used alone can be achieved. As a result, swelling of the hydrophilic resin in the first barrier layer is suppressed, and high oxygen barrier properties can be maintained even under high humidity conditions or after bending. Due to the above effects, it is possible to realize a laminate that has excellent oxygen barrier properties under high humidity conditions and after bending, as well as excellent blocking resistance. Note that these speculations do not limit the invention in any way.
[0024] Specific examples of the laminate structure include, but are not limited to, the following structures. In the following structure notation, " / " means the boundary between layers. The adhesive layer is not limited to the adhesive used in the conventionally known methods of dry lamination and non-sol lamination, but also includes polyolefin resin and other thermoplastic resin layers in extrusion lamination. The names of each layer are functional in terms of the form of use, and the substrate, sealant, thermoplastic resin layer, heat sealant layer, and intermediate substrate may not be distinguishable from the viewpoint of materials, except when they are in direct contact. In the following structure, AC layer indicates an anchor coat layer. (1) Second barrier layer / first barrier layer / printed layer / substrate (2) Second barrier layer / first barrier layer / printed layer / substrate / thermoplastic resin layer (3) Second barrier layer / first barrier layer / printing layer / substrate / adhesive layer / sealant (4) Second barrier layer / first barrier layer / printing layer / substrate / adhesive layer / intermediate substrate / adhesive layer / sealant (5) Second barrier layer / First barrier layer / Printed layer / Substrate / Adhesive layer / First intermediate substrate / Adhesive layer / Second intermediate substrate / Adhesive layer / Sealant (6) Second barrier layer / substrate / printed layer / first barrier layer / thermoplastic resin layer (7) Second barrier layer / substrate / printed layer / first barrier layer / adhesive layer / sealant (8) Second barrier layer / substrate / printed layer / first barrier layer / adhesive layer / intermediate substrate / adhesive layer / sealant (9) Second barrier layer / substrate / printed layer / first barrier layer / adhesive layer / first intermediate substrate / adhesive layer / second intermediate substrate / adhesive layer / sealant (10) Second barrier layer / first barrier layer / AC layer / printing layer / substrate / adhesive layer / sealant (11) Second barrier layer / substrate / printed layer / AC layer / first barrier layer / adhesive layer / sealant (12) Second barrier layer / substrate / AC layer / printed layer / first barrier layer / thermoplastic resin layer (13) Second barrier layer / AC layer / substrate / printed layer / first barrier layer / adhesive layer / sealant (14) Second barrier layer / AC layer / substrate / AC layer / printed layer / first barrier layer / adhesive layer / sealant (15) Second barrier layer / AC layer / substrate / printed layer / AC layer / first barrier layer / adhesive layer / sealant However, the present invention is not limited to these forms.
[0025] A preferred laminate structure of the laminate of the present invention is a structure having a substrate, a first barrier layer, and a second barrier layer in this order, or a structure having a first barrier layer, a substrate, and a second barrier layer in this order. It is more preferred that the laminate further includes an anchor coat layer, and examples thereof include a structure having a substrate, an anchor coat layer, a first barrier layer, and a second barrier layer in this order, a structure having a first barrier layer, an anchor coat layer, a substrate, and a second barrier layer in this order, a structure having a first barrier layer, a substrate, an anchor coat layer, and a second barrier layer in this order, and a structure having a first barrier layer, an anchor coat layer, a substrate, an anchor coat layer, and a second barrier layer in this order.
[0026] [Base material] The substrate is not particularly limited, but is preferably the following embodiment. That is, for example, the paper substrate may be medium-quality paper, fine paper, impregnated paper, cardboard, or kraft paper, and the plastic substrate may be polyethylene such as biaxially oriented polypropylene (OPP), non-oriented polypropylene (CPP), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), or high-density polyethylene (HDPE), acid-modified polyethylene, acid-modified polypropylene, copolymerized polypropylene, polyethylene terephthalate, polycarbonate, polylactic acid, polystyrene, AS resin, ABS resin, nylon, polyamide, polyvinyl chloride, polyvinylidene chloride, or cellophane, and the substrate made of the above composite material may also be used. In addition, the substrate may be subjected to deposition of inorganic compounds such as silica, alumina, or aluminum, or to coating treatment such as polyethylene or polyvinyl alcohol, or may be subjected to corona treatment. Among them, the substrate is preferably a paper substrate or a plastic substrate, and more preferably a paper substrate or a stretched plastic substrate.
[0027] In the case of a plastic substrate, the thickness of the substrate is not particularly limited, but taking into consideration processability into packaging containers and the like, the thickness is preferably 5 μm or more and 150 μm or less, more preferably 10 μm or more and 70 μm or less.
[0028] In the case of a paper substrate, the basis weight of the substrate is not particularly limited and can be appropriately selected depending on the various qualities and handling properties desired for the barrier material, but is preferably 20 to 600 g / m 2 For packaging materials used for packaging purposes such as food packaging, bags, paper containers, cardboard boxes, cups, etc., the maximum is 25 to 600 g / m 2 The following is more preferable. The above basis weight is further preferably 30 to 400 g / m 2 and more preferably 40 to 200 g / m 2 and particularly preferably 50 to 100 / m 2 It is.
[0029] The substrate may be a single layer, may be simply a laminate of plastic substrates, or may be a laminate of a substrate different from the plastic substrate via an adhesive layer or the like. The "substrate different from the plastic substrate" may be a plastic substrate or a paper substrate having different properties, and may be of any type. In addition, the substrate may be a laminated substrate including an adhesive layer. The method of laminating the substrate is not particularly limited, and may be a conventionally known method such as a co-extrusion method, heat fusion, or pressure bonding via an adhesive layer.
[0030] [First barrier layer] The first barrier layer is provided for the purpose of imparting oxygen barrier properties to the laminate, and the barrier layer contains a hydrophilic resin. The first barrier layer is preferably formed by applying a first barrier coating agent described later onto the substrate, an anchor coat layer described later, or a second barrier layer described later, and removing volatile components. The mass per unit area of the first barrier layer is 0.1 to 20 g / m 2 is preferably 0.3 to 17 g / m 2 More preferably, the thickness is 0.5 to 15 g / m 2 More preferably, the thickness is 0.6 to 10 g / m 2 It is particularly preferable that the thickness is 0.7 to 5 g / m 2 When the mass per unit area of the first barrier layer is within the above range, the oxygen barrier property is excellent.
[0031] In particular, when the substrate is a plastic substrate, the mass per unit area of the first barrier layer is 0.1 to 20 g / m 2 It is preferable that the thickness is 0.3 to 10 g / m 2 More preferably, the thickness is 0.5 to 5 g / m 2 More preferably, the thickness is 0.6 to 3 g / m 2 When the substrate is a plastic substrate, if the mass per unit area of the first barrier layer is within the above range, the oxygen barrier property is good.
[0032] In particular, when the substrate is a paper substrate, the mass per unit area of the first barrier layer is 0.1 to 20 g / m 2 It is preferable that the thickness is 0.5 to 10 g / m 2 More preferably, the thickness is 0.7 to 7 g / m 2 More preferably, the density is 1 to 5 g / m 2 When the substrate is a paper substrate, if the mass per unit area of the first barrier layer is within the above range, the oxygen barrier property is good.
[0033] <Hydrophilic resin> The hydrophilic resin refers to a resin that is miscible with an aqueous solvent, which will be described later. Examples of the hydrophilic resin include polyvinyl alcohol resins (including ethylene vinyl alcohol copolymer resins), aqueous acrylic resins, aqueous styrene-acrylic resins, aqueous styrene-maleic acid resins, aqueous urethane resins, aqueous polylactic acid resins, and modified resins thereof. These hydrophilic resins can be used alone or in combination of two or more. Among the above, the hydrophilic resin preferably contains a polyvinyl alcohol resin.
[0034] The content of the hydrophilic resin in the total mass of the first barrier layer is preferably 30 to 95% by mass, more preferably 55 to 90% by mass, and even more preferably 70 to 80% by mass, in order to improve the oxygen barrier property after bending.
[0035] <Polyvinyl alcohol resin> The polyvinyl alcohol resin may be any resin having a vinyl alcohol unit, and further preferably contains a structural unit derived from ethylene. Examples of polyvinyl alcohol resins include polyvinyl alcohol resins and ethylene-vinyl alcohol copolymer resins, with polyvinyl alcohol resins and / or ethylene-vinyl alcohol copolymer resins being preferred, and ethylene-vinyl alcohol copolymer resins being more preferred.
[0036] The content of ethylene-derived structural units in the ethylene-vinyl alcohol copolymer resin is preferably 1 to 40 mol%, more preferably 3 to 20 mol%, and even more preferably 5 to 15 mol%. When the content of ethylene-derived structural units is within the above range, the oxygen barrier property after bending is good. The polymerization degree of the polyvinyl alcohol resin is preferably 100 to 3,000, and more preferably 500 to 2,400. When the polymerization degree of the polyvinyl alcohol resin is within the above range, the oxygen barrier property after bending is good.
[0037] The polyvinyl alcohol resin may have a modified functional group, and examples of the functional group include, but are not limited to, a carbonyl group, a silicon group, etc. Also, the polyvinyl alcohol resin may be used that has been crosslinked with a crosslinking agent, and examples of the crosslinking agent used include known crosslinking agents such as an isocyanate crosslinking agent, an epoxy crosslinking agent, a melamine crosslinking agent, an oxazoline crosslinking agent, and a silane coupling crosslinking agent, and the oxazoline crosslinking agent and the silane coupling crosslinking agent are preferred.
[0038] The degree of saponification of the polyvinyl alcohol-based resin is represented by the following formula (1), and is preferably 80 mol% or more, more preferably 90 mol%, and more preferably 95 mol%. When the degree of saponification of the polyvinyl alcohol-based resin is within the above range, the oxygen barrier property is good. (Formula 1) Saponification degree: (number of hydroxyl groups) / {(number of hydroxyl groups)+(number of acetate groups)}×100 [mol %]
[0039] As the polyvinyl alcohol-based resin, Kuraray Poval R series (polyvinyl alcohol resin, manufactured by Kuraray Co., Ltd.), Kuraray Eval L104B, F104B (ethylene-vinyl alcohol copolymer resin, manufactured by Kuraray Co., Ltd.), etc. can be used.
[0040] The first barrier layer may contain a resin other than the polyvinyl alcohol resin, and specific examples include polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, acrylic resin, etc. These resins may be used alone or in combination of two or more.
[0041] <Inorganic layered filler> The first barrier layer preferably contains an inorganic layered filler. The inorganic layered filler here refers to an inorganic filler in which single crystal layers are stacked to form a layered structure, and is particularly preferably one that swells and / or cleaves in a solvent. The mass ratio of the hydrophilic resin to the inorganic layered filler is preferably 4:6 to 9:1, more preferably 6:4 to 8:2, and even more preferably 8:2 to 7:3. When the mass ratio of the hydrophilic resin to the inorganic layered filler is within the above range, the oxygen barrier property and blocking resistance after bending are good.
[0042] Preferred examples of the inorganic layered filler include montmorillonite, beidellite, saponite, hectorite, sauconite, vermiculite, mica, paragonite, lepidolite, margarite, clintonite, anandite, chlorite, donbassite, sudoite, cookeite, clinochlore, chamosite, nimite, tetrasilylic mica, talc, pyrophyllite, nacrite, kaolinite, halloysite, chrysotile, sodium teniolite, xanthophyllite, antigorite, dickite, hydrotalcite, etc., and one or more selected from the group consisting of kaolin, montmorillonite, and mica are preferred, and montmorillonite is more preferred. Montmorillonite has high water absorption and high viscosity after swelling due to its layered structure, so that resin easily penetrates between the layers of the layered filler, contributing to improving the oxygen barrier property of the laminate.
[0043] These inorganic layered fillers may be naturally occurring or artificially synthesized or modified, or may be treated with an organic substance such as an onium salt.
[0044] The content of the inorganic layered filler is preferably 1 to 40 mass %, more preferably 10 to 35 mass %, and further preferably 20 to 30 mass %, in 100 mass % of the first barrier layer.
[0045] <Montmorillonite> The above montmorillonite is represented by the following formula 2. Bentonite, which contains montmorillonite as a main component and further contains minerals such as quartz and feldspar, can also be preferably used. (Formula 2) M a Si4(Al 2-a Mg a )O 10 (OH)2 nH2O (In formula 2, M represents a sodium cation, and a is 0.25 to 0.60. The number of water molecules bonded to the ion-exchangeable cations between layers can vary depending on the cation species, humidity, and other conditions, and is therefore represented by nH2O in the formula.)
[0046] Montmorillonite also includes isomorphous ion-substituted products of magnesian montmorillonite, iron montmorillonite, and iron magnesian montmorillonite, which are represented by the following formulas (3) to (5), and these may also be used. (Formula 3) M a Si4(Al 1.67-a Mg 0.5+a )O 10 (OH)2 nH2O (Formula 4) M a Si4(Fe 2-a3 +Mg a )O 10 (OH)2 nH2O (Formula 5) M a Si4(Fe 1.67-a3 +Mg 0.5+a )O 10 (OH)2 nH2O (In formulas 3 to 5, M represents a sodium cation, and a is 0.25 to 0.60.)
[0047] Montmorillonite usually has cations between its layers, but the content varies depending on the place of origin. Examples of the ions include inorganic cations such as sodium ions, calcium ions, magnesium ions, and potassium ions, and organic cations such as quaternary ammonium ions. From the viewpoint of affinity with water, inorganic cations are preferred, and sodium ions and / or calcium ions are more preferred. It is also preferred to use montmorillonite that has been purified by water treatment.
[0048] The volume-average particle thickness of montmorillonite is preferably 0.05 to 30 nm, more preferably 0.1 to 10 nm, and even more preferably 0.5 to 3 nm. The volume-average particle major axis of montmorillonite is preferably 0.01 to 5 μm, more preferably 0.05 to 3 μm, and even more preferably 0.1 to 1 μm. In addition, the volume-average particle aspect ratio of montmorillonite is preferably 10 to 2,000, more preferably 100 to 1,000, and even more preferably 300 to 700. In the present invention, the particle thickness, particle major axis, and particle aspect ratio of montmorillonite can be measured by an atomic force microscope (AFM).
[0049] As the montmorillonite, commercially available products such as Kunipia-F and Kunipia-G (manufactured by Kunimine Kogyo Co., Ltd.) can be used.
[0050] <Kaolin> Kaolin is mainly composed of kaolinite (Al2O3·2SiO2·H2O) or halloysite (Al2O3·2SiO2·2H2O) and may be natural or synthetic. Depending on the manufacturing method, there are dry kaolin, wet kaolin, calcined kaolin, etc., but it is not limited to these.
[0051] From the viewpoint of oxygen barrier property, the volume-average particle size of kaolin is preferably 1 to 100 μm, more preferably 3 to 50 μm, and even more preferably 5 to 20. The volume-average aspect ratio of kaolin is preferably 10 to 1,000, more preferably 30 to 500, and even more preferably 50 to 200. In the present invention, the particle size of kaolin can be measured by a laser analysis / scattering method, and the aspect ratio can be measured by a scanning electron microscope (SEM).
[0052] As the kaolin, commercially available products such as Varisurf HX (manufactured by Imerys), NN kaolin clay, and ST kaolin clay (manufactured by Takehara Chemical Industry Co., Ltd.) can be used.
[0053] <Mica> Both natural and synthetic mica can be used. Natural mica is a scaly base material made by crushing mica ore, and the particle size and aspect ratio can be controlled by mechanical crushing, cleavage by calcination, etc. Synthetic mica includes those synthesized by heating industrial raw materials such as SiO2, MgO, Al2O3, K2SiF6, Na2SiF6, etc., melting them at a high temperature of about 1500°C, and then cooling and crystallizing them, and compared to natural mica, it has fewer impurities and is more uniform in size and thickness. Specifically, fluorine mica (KMg3AlSi3O10F2), potassium tetrasilicic mica (KMg 25 AlSi4O10F2), sodium tetrasilicic mica (NaMg 25 AlSiO 10 F2), Na taeniolite (NaMg2LiSi4O10F2), LiNa taeniolite (LiMg2LiSi4O 10 F2) are known. From the viewpoint of dispersibility, synthetic mica that is easy to cleave by intercalation is preferable.
[0054] From the viewpoints of printability and oxygen barrier properties of the barrier coating agent, the volume average particle size of the mica is preferably 30 μm or less, more preferably 1 to 25 μm, and even more preferably 5 to 15 μm. The volume average aspect ratio of the mica is preferably 30 to 200, more preferably 70 to 170, and even more preferably 100 to 150. In the present invention, the particle size of mica can be measured by a laser analysis / scattering method, and the aspect ratio can be measured by a scanning electron microscope (SEM).
[0055] As the mica, commercially available products such as Mica Powder TM series, Mica Powder NCF series (manufactured by Yamaguchi Mica Co., Ltd.), L60M, L100M (manufactured by Seishin Enterprise Co., Ltd.) and the like can be used.
[0056] <Additives contained in the first barrier layer> The first barrier layer may contain known additives such as an isocyanate compound, a silane coupling agent, a dispersant, a stabilizer, a viscosity adjuster, a colorant, etc., within the scope of not impairing the effects of the present invention.
[0057] <First Barrier Coating Agent for Forming First Barrier Layer> The first barrier layer is preferably formed by a first barrier coating agent. The first barrier coating agent preferably contains a hydrophilic resin and further contains an aqueous solvent. Furthermore, each component of the inorganic layered filler can be added to the coating agent alone or in combination, and additives contained in the first barrier layer can be added appropriately. The first barrier coating agent can be obtained by charging a resin solution in which a resin is dissolved or dispersed in an aqueous solvent, and an aqueous solvent into a mixer equipped with a stirring blade, a rotor, etc., and mixing and stirring them. There is no particular restriction on the stirring speed, and stirring can be performed at 50 to 2000 rpm. In order to improve the handling and oxygen barrier properties of the first barrier coating agent, inorganic layered fillers, various additives, and an aqueous solvent can also be appropriately added.
[0058] <Aqueous solvent> The first barrier coating agent preferably contains an aqueous solvent. The main component of the aqueous solvent is preferably water, but a hydrophilic organic solvent can be used in addition to water. Specifically, an alcohol-based organic solvent, a glycol-based organic solvent, etc. can be contained depending on the printing conditions (speed, plate depth, design, drying temperature). In the present invention, the term "mainly water" means that the content of water is the largest in the aqueous solvent, and the term "hydrophilic organic solvent" means that the solvent is liquid at 25° C. and has a solubility of 1% by mass or more in water at 25° C.
[0059] <Formation of the first barrier layer> The first barrier layer can be formed, for example, by printing the first barrier coating agent on the substrate, the anchor coat layer described later, or the second barrier layer described later, and then removing the volatile components. Printing methods include conventionally known methods such as gravure printing, flexographic printing, dipping, roll coating, screen printing, and spraying, but the gravure printing method is preferred. For example, the agent is diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing, and is supplied to each printing unit alone or in a mixture and applied. Thereafter, the coating is fixed by drying in an oven or the like to obtain an oxygen barrier coat layer.
[0060] [Second barrier layer] The second barrier layer is provided for the purpose of imparting water vapor barrier properties to the laminate, and contains a thermoplastic styrene elastomer and a hydrocarbon wax. The second barrier layer is preferably formed by applying a second barrier coating agent described below onto the substrate, an anchor coating layer described below, or the first barrier coating layer, and removing volatile components.
[0061] The mass per unit area of the second barrier layer is 0.1 to 20 g / m 2 is preferably 0.3 to 17 g / m 2 More preferably, the thickness is 0.5 to 15 g / m2 More preferably, the thickness is 3 to 14 g / m 2 It is particularly preferable that the thickness is 7 to 13 g / m 2 When the mass per unit area of the second barrier layer is within the above range, the oxygen barrier property is excellent.
[0062] <Thermoplastic styrene elastomer> The thermoplastic styrene elastomer may be a thermoplastic polymer containing a structural unit derived from a styrene monomer. The thermoplastic styrene elastomer may contain a structural unit derived from a monomer such as a styrene monomer, an acrylic monomer, or a hydrocarbon monomer, and may be in the form of a block copolymer or a core-shell structure, and a preferred form is a styrene block copolymer. The thermoplastic styrene elastomer is preferably appropriately compatible with the hydrocarbon wax described below when a solvent described below is added to prepare a second barrier coating agent.
[0063] <Styrene-based block copolymer> Styrene block copolymers generally have a polystyrene block and a rubber middle block, with the polystyrene portion forming a physical crosslink (domain) and becoming the crosslinking point, and the middle rubber block giving the product rubber elasticity. The middle soft segment includes polybutadiene (B), isobutylene (IB), polyisoprene (I) and polyolefin elastomer (ethylene propylene, EP), etc., and depending on the arrangement with the hard segment polystyrene (S), they are divided into linear type and radial type.
[0064] The thermoplastic styrene elastomer preferably contains, as a styrene-based block copolymer, at least one selected from the group consisting of styrene-isobutylene-styrene block copolymer (SIBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butylene-styrene block copolymer (SBS), styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-isoprene-styrene block copolymer (SBIS), hydrogenated styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), and styrene-butadiene copolymer (SB), as well as their acid-modified, acid anhydride-modified, and amine-modified counterparts. However, the present invention is not limited to these resins.
[0065] Among the above styrene-based block copolymers, one or more selected from the group consisting of styrene-isobutylene-styrene block copolymers (SIBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-butylene-styrene block copolymers (SEBS), hydrogenated styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), and acid-modified, acid anhydride-modified, and amine-modified versions thereof are preferred, and one or more selected from the group consisting of styrene-isobutylene-styrene block copolymers (SIBS), styrene-ethylene-butylene-styrene block copolymers (SEBS), and acid-modified, acid anhydride-modified, and amine-modified versions thereof are more preferred.
[0066] The mass average molecular weight of the thermoplastic styrene elastomer is preferably 10,000 to 200,0000, more preferably 30,000 to 170,000, and even more preferably 60,000 to 130,000. When the mass average molecular weight of the thermoplastic styrene elastomer is within the above range, the oxygen barrier property after bending is improved.
[0067] The content of styrene in the thermoplastic styrene elastomer is preferably 5 to 65 mass%, more preferably 15 to 50 mass%, and even more preferably 25 to 35 mass%, based on 100 mass% of the thermoplastic styrene elastomer. When the content of styrene in the thermoplastic styrene elastomer is within the above range, the oxygen barrier property after bending is improved.
[0068] The content of the acid-modified product, the acid anhydride-modified product, and the amine-modified product in the thermoplastic styrene elastomer is preferably 0.01 to 10 mass%, more preferably 0.1 to 5 mass%, and further preferably 0.5 to 3 mass%, based on 100 mass% of the thermoplastic styrene elastomer. When the content of the acid-modified product, the acid anhydride-modified product, and the amine-modified product in the thermoplastic styrene elastomer is within the above range, the oxygen barrier property after bending is improved.
[0069] The content of the thermoplastic styrene elastomer is preferably 30 to 90 mass %, more preferably 40 to 80 mass %, and even more preferably 50 to 70 mass %, of the total mass of the second barrier layer. When the content of the thermoplastic styrene elastomer is within the above range, the oxygen barrier property is improved.
[0070] Commercially available thermoplastic styrene elastomers include, for example, FG1901, FG1924, G1650, D1117, G1643, FG1924, and MD1648 manufactured by Kraton Corporation, and AR-GB-40, AR-1040, AR-NF0-80B, AR-815, and AR-8050NC manufactured by Aron Chemical Industries, Ltd.
[0071] <Hydrocarbon wax> The hydrocarbon wax refers to an organic substance that is mainly composed of a long-chain alkyl group skeleton, is solid at room temperature, and becomes liquid when heated, and may contain an acid group, an ester group, a hydroxyl group, etc., in the skeleton. By combining such a hydrocarbon wax with a thermoplastic styrene elastomer, it becomes possible to achieve high water vapor barrier properties that could not be observed with either resin alone. Here, the factor behind the development of water vapor barrier properties resulting from the combination of a hydrocarbon wax and a thermoplastic styrene elastomer is presumed to be as follows. That is, the second barrier coating agent described below is applied to a substrate and then undergoes a heat drying process to form a second barrier layer, and in the heat drying process, the hydrocarbon wax contained in the second barrier coating agent begins to aggregate and form aggregates. Furthermore, in the process of the hydrocarbon waxes aggregating together, it is believed that an oriented structure or crystalline structure resulting from the high crystallinity of the hydrocarbon wax is formed on the surface. Although the details are unclear, it is believed that the appropriate compatibility between the hydrocarbon wax and the thermoplastic styrene elastomer plays an important role in the formation of the above-mentioned aggregates. As a result, a dense wax layer is formed within the water vapor barrier coat layer, particularly near the interface and surface. The presence of hydrophobic and highly crystalline areas that are difficult for water vapor to permeate inhibits the dissolution and diffusion of water vapor, resulting in excellent water vapor barrier properties.
[0072] Examples of the hydrocarbon wax include, but are not limited to, one or more selected from the group consisting of natural waxes and synthetic waxes such as paraffin wax, microcrystalline wax, beeswax, montan wax, ozokerite, ceresin, carnauba wax, candelilla wax, beeswax, Japan wax, and rice wax. The hydrocarbon wax is preferably dissolved uniformly in the second barrier coating agent described below.
[0073] Examples of commercially available hydrocarbon waxes include natural waxes such as paraffin wax and microcrystalline wax manufactured by Nippon Seiro Co., Ltd. and ENEOS Corp. Examples of synthetic waxes include FT115, FT0165, SX105, and FNP0090 manufactured by Nippon Seiro Co., Ltd., CERAMER polymer, POLYWAX polyethylene, UNICID carboxylic acid, UNILIN alcohol, UNITHOX ethoxylate, PETROLITE copolymer, and VYBAR polymer manufactured by Baker Hughes Co., Ltd., Diacarna manufactured by Mitsubishi Chemical Corporation, and the Sunwax series and Viscol series manufactured by Sanyo Chemical Co., Ltd.
[0074] From the viewpoint of water vapor barrier properties, the melting point of the hydrocarbon wax is preferably 30°C or higher and 110°C or lower, and more preferably 40°C or higher and 90°C or lower. In addition, it is preferable that 80% or more of the hydrocarbon wax has a linear structure without branches, and more preferably 90% or more has a linear structure without branches. When the proportion of linear structures is within the above range, the crystallinity of the hydrocarbon wax is improved, so that the water vapor barrier property of the second barrier layer is improved, and the oxygen barrier property of the laminate under high humidity conditions is improved.
[0075] Further, examples of hydrocarbon waxes that are solid at room temperature and have a melting point of 30° C. to 110° C. include waxy olefins having double bonds in the molecule, which may be used in combination with other waxes.
[0076] Among the hydrocarbon waxes, paraffin wax and microcrystalline wax are preferred, and paraffin wax is most preferred. These waxes have excellent crystallinity and can particularly promote the formation of the wax aggregate structure described above, improving the water vapor barrier property of the second barrier layer and making it possible to suppress the decrease in the oxygen barrier property of the laminate under high humidity conditions.
[0077] The content of the hydrocarbon wax is preferably 5 to 50 mass %, more preferably 10 to 50 mass %, and even more preferably 20 to 40 mass %, of the total mass of the second barrier layer. By having the content of the hydrocarbon wax in the above range, better water vapor barrier properties are exhibited, and it becomes possible to suppress a decrease in the oxygen barrier properties of the laminate under high humidity conditions.
[0078] The mass ratio of the thermoplastic styrene elastomer to the hydrocarbon wax in the second barrier layer is preferably 95:5 to 30:70, more preferably 85:15 to 40:60, and even more preferably 75:25 to 55:45. When the mass ratio of the thermoplastic styrene elastomer to the hydrocarbon wax in the second barrier layer is within the above range, the oxygen barrier property is improved.
[0079] <Extender pigment> The second barrier layer preferably further contains a body pigment. The body pigment contained in the barrier layer may be the same as or different from the inorganic layered filler described in the first barrier layer. Specific examples of the body pigment include silica, calcium carbonate, barium sulfate, montmorillonite, and kaolin, and silica is preferred.
[0080] The content of the extender pigment is preferably 1 to 30% by mass, and more preferably 5 to 10% by mass, when the total solid content of the second barrier layer is taken as 100% by mass. By having the content of the extender pigment in this range, it is possible to achieve better blocking resistance while maintaining oxygen barrier properties.
[0081] <Silica> From the viewpoint of blocking resistance, the extender pigment is preferably silica. Examples of silica include natural or synthetic products, crystalline or non-crystalline, hydrophobic or hydrophilic.Silica can be synthesized by dry or wet methods, and the dry methods include combustion method and arc method, and the wet methods include precipitation method and gel method, and it can be synthesized by either method.In addition, silica can be hydrophilic silica having hydrophilic functional groups on the surface, or hydrophobic silica in which hydrophilic functional groups are modified with alkylsilane or the like to be hydrophobic, but it is preferable to use hydrophilic silica. Commercially available silica products include, for example, the Nipgel series and Nipsil series manufactured by Tosoh Silica Corporation, and the Mizukasil series manufactured by Mizusawa Chemical Industries, Ltd.
[0082] In order to improve blocking resistance, the silica has an average particle size of preferably 1 to 10 μm, more preferably 1 to 8 μm, and even more preferably 1 to 6 μm. The average particle size of silica means the particle size at an integrated value of 50% (D50) in the particle size distribution, and was determined by a laser scattering method. The specific surface area of silica is 50 to 600 m by the BET method. 2 / g, and 100 to 450m 2 It is more preferable that the average particle size or the BET specific surface area of the silica is different from that of the silica of the present invention.
[0083] <Second Barrier Coating Agent for Forming Second Barrier Layer> The second barrier layer is preferably formed by a second barrier coating agent. The second barrier coating agent can be obtained, for example, by stirring and mixing optional components such as a thermoplastic styrene elastomer, a hydrocarbon wax, and other optional components such as a solvent, using a roll, a stirrer, a melting furnace, or the like. However, the production method is not particularly limited, and any method may be used as long as these components can be mixed uniformly. Furthermore, in order to mix each component uniformly, a dispersion treatment may be performed using a planetary mixer, a disperser, a sand mill, etc. In the above stirring and dispersion steps, the thermoplastic styrene elastomer and the hydrocarbon wax do not necessarily have to be completely dissolved, and may form a fine particle emulsion.
[0084] <Solvent> From the viewpoint of imparting coating suitability, the second barrier coating agent preferably further contains a solvent. As the solvent, for example, known organic solvents can be used, such as ester-based solvents such as methyl acetate, ethyl acetate, and normal propyl acetate, alcohol-based solvents such as methyl alcohol, ethyl alcohol, and isopropyl alcohol, ketone-based solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone, and hydrocarbon-based solvents such as toluene, benzene, cyclohexane, hexane, methylcyclohexane, and ethylcyclohexane. These can also be used alone or in combination of two or more.
[0085] Of these solvents, in order to form the aforementioned hydrocarbon wax aggregate structure, it is preferable to use an organic solvent whose Hansen solubility parameter (HSP value) dispersion term δd is 14 or more and whose dipole term δp is 3 or less, because this has a relatively high compatibility with the styrene-based thermoplastic resin and / or the hydrocarbon wax in the second barrier coating agent and can facilitate crystallization and surface migration of the hydrocarbon wax after drying. It is even more preferable to use an organic solvent whose dispersion term δd is 15 or more and whose dipole term δp is 4 or less, and it is preferable that the solvent contains 50% or more of an organic solvent having these specific HSP values.
[0086] Examples of organic solvents having an HSP value of a dispersion force term δd of 15 or more and a dipole-dipole force term δp of 4 or less include non-polar solvents such as toluene, methylcyclohexane, cyclohexane, heptane, octane, and hexane.
[0087] The HSP value is the solubility parameter introduced by Hildebrand, divided into three components: the dispersion force term δd, the polarity term δp, and the hydrogen bond term δh, and takes into account the polarity of the substance. The HSP value may be a publicly known value, or it may be calculated using the computer software HSPiP (source: http: / / www.hansen-solubility.com / index.html).
[0088] The content of the solvent is not particularly limited, but is preferably 50 to 95 mass% in 100 mass% of the water vapor barrier composition. Furthermore, when an organic solvent is used, the content of the organic solvent is preferably 50 to 100 mass% in 100 mass% of the solvent.
[0089] <Other ingredients> The second barrier coating agent may contain various additives as appropriate, provided that the effects of the present invention are not impaired. For example, curing agents such as polyisocyanate, epoxy resin, and polycarbodiimide compounds, organic or inorganic fillers, liquid rubber, silane coupling agents, titanate coupling agents, flame retardants, storage stabilizers, antioxidants, metal deactivators, UV absorbers, thixotropy-imparting agents, leveling agents, defoamers, dispersion stabilizers, fluidity-imparting agents, defoamers, and coloring materials may be added. Liquid rubber or softeners may also be added to improve fluidity and adhesion.
[0090] <Formation of the second barrier layer> The second barrier layer can be formed, for example, by printing the second barrier coating agent on the anchor coat layer and then removing the volatile components. The printing method includes conventionally known methods such as gravure printing, flexographic printing, dipping, roll coating, screen printing, and spraying, but the gravure printing method is preferred. For example, the agent is diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing, and is supplied to each printing unit alone or in a mixture and applied. The coating is then fixed by drying in an oven or the like to obtain the second barrier layer.
[0091] [Anchor coat layer] The anchor coat layer is located between the substrate and the first barrier layer, and / or between the substrate and the second barrier layer, and improves the adhesion of the first barrier layer and / or the second barrier layer to the substrate. When a paper substrate is used as the substrate, the anchor coat layer acts as a filler, reducing the penetration of the first barrier layer and / or the second barrier layer into the paper substrate, and forming a coating film with high smoothness and few pinholes, which contributes to improving the oxygen barrier property. Note that, depending on the layered structure, such as a laminate having a first barrier layer, a substrate, and a second barrier layer in this order, there may be multiple anchor coat layers, but the multiple anchor coat layers may all be the same or different from each other. In this specification, an anchor coat layer formed with an oil-based anchor coat agent is referred to as an oil-based anchor coat layer, and an anchor coat layer formed with an aqueous anchor coat agent is referred to as an aqueous anchor coat layer. The anchor coat layer may be an oil-based anchor coat layer or an aqueous anchor coat layer. The mass per unit area of the anchor coat layer is not particularly limited, but is preferably 0.5 to 10.0 g / m in a dry state. 2 is preferably 1.0 to 7.0 g / m 2 More preferably, 1.5 to 6.5 g / m 2 When the mass per unit area of the anchor coat layer is within the above range, the oxygen barrier property after bending is improved.
[0092] <Urethane resin> The anchor coat layer preferably contains a urethane resin, and the urethane resin refers to an oil-based urethane resin described in <Resin contained in oil-based anchor coat layer> below, and an aqueous urethane resin described in <Resin contained in aqueous anchor coat layer> below. The urea bond concentration of the urethane resin is 0.1 to 1.3 mmol / g, more preferably 0.3 to 1.15 mmol / g, and even more preferably 0.6 to 0.9 mmol / g. The urethane bond concentration of the urethane resin is preferably 0.1 to 1.3 mmol / g, more preferably 0.3 to 1.15 mmol / g, and even more preferably 0.6 to 0.9 mmol / g. When the urea bond concentration and urethane bond concentration of the urethane resin are within the above ranges, the oxygen barrier property after bending is good.
[0093] (Urethane bond concentration) Here, the urethane bond concentration is a value expressed as follows. In the raw materials constituting the urethane resin, when (number of moles of NCO / number of moles of OH)>1, the urethane bond concentration is expressed by the following (Equation 7). (Formula 7) Urethane bond concentration (mmol / g) = total number of moles of hydroxyl groups (mmol) / total mass of solids (g) Here, the total number of moles of hydroxyl groups refers to the total number of moles of hydroxyl groups contained in polyols and the like used in the reaction to form urethane, and the total solid content refers to the total mass of non-volatile components that become the urethane resin.
[0094] In the raw materials constituting the urethane resin, when (number of moles of NCO / number of moles of OH) is less than 1, the urethane bond concentration is expressed by the following formula (8). (Formula 8) Urethane bond concentration (mmol / g) = total number of moles of isocyanate groups (mmol) / total mass of solids (g) The total number of moles of isocyanate groups herein refers to the total number of moles of isocyanate groups contained in the polyisocyanate used in the reaction to form urethane.
[0095] (urea bond concentration) Here, the urea binding concentration is a value expressed as follows. When a prepolymer having a terminal isocyanate group is synthesized under conditions such that (number of moles of NCO / number of moles of OH)>1, and then chain-extended with polyamine to give a urethane resin having an amino group at its terminal, the urea bond concentration is expressed by the following formula (9). (Formula 9) Urea bond concentration (mmol / g) = [total number of moles of isocyanate groups (mmol) - total number of moles of hydroxyl groups (mmol)] / total mass of solids (g)
[0096] When a prepolymer having a terminal isocyanate group is synthesized under conditions such that (number of moles of NCO / number of moles of OH)>1, and then chain-extended with polyamine to give a urethane resin having an isocyanate group at its terminal, the urea bond concentration is expressed by the following formula (10). (Formula 10) Urea bond concentration (mmol / g) = (total number of amino group moles (mmol)) / total mass of solids (g) The total number of moles of amino groups herein refers to the total number of moles of primary or secondary amino groups contained in the polyamine used to form urea bonds by reacting with a prepolymer having a terminal isocyanate group.
[0097] <Resin contained in oil-based anchor coat layer> When the anchor coat layer is an oil-based anchor coat layer, it is preferable to include an oil-based resin, and examples of the oil-based resin include urethane resin, cellulose resin, polylactic acid resin, polyamide resin, vinyl chloride resin, rosin resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, acrylic resin, styrene resin, butyral, polyacetal resin, and modified resins thereof, and these resins can be used alone or in combination of two or more. Urethane resin, cellulose resin, polylactic acid resin, and vinyl chloride resin are preferred, and urethane resin is more preferred.
[0098] <Oil-based urethane resin> As the oil-based urethane resin, for example, one produced by the method described in JP 2013-256551 A can be used, and preferred are urethane resins made of polyol and polyisocyanate, and urethane resins obtained by reacting a urethane prepolymer having a terminal isocyanate, made of polyol and polyisocyanate, with a polyamine.
[0099] The mass average molecular weight of the oil-based urethane resin is preferably 10,000 to 100,000, more preferably 20,000 to 85,000, and even more preferably 30,000 to 70,000. When the mass average molecular weight of the oil-based urethane resin is in the above range, the oxygen barrier property after bending is good. The glass transition temperature of the oil-based urethane resin is preferably -80 to 20°C, more preferably -60 to 0°C, and even more preferably -40 to -5°C. When the glass transition temperature of the oil-based urethane resin is in the above range, the oxygen barrier property after bending is good. In addition, the oil-based urethane resin preferably has an amino group and / or a hydroxyl group, and when it has an amino group, the amine value is preferably 0.5 to 30 mgKOH / g, and more preferably 1 to 20 mgKOH / g. In addition, when the oil-based urethane resin has a hydroxyl group, the hydroxyl value is preferably 0.5 to 30 mgKOH / g, more preferably 1 to 20 mgKOH / g. When it is within the above range, the oxygen barrier property after bending is improved. The preferred form of the number of urea bonds in the oil-based urethane resin is as described above in the explanation of <Urethane resin>.
[0100] The oil-based urethane resin preferably contains structural units derived from polyether polyol and / or polyester polyol, and the total content thereof is preferably 5 to 80 mass%, more preferably 10 to 60 mass%, and even more preferably 10 to 50 mass%, based on 100 mass% of the urethane resin solid content.
[0101] The oil-based urethane resin preferably contains a structural unit derived from polyester polyol, and the content thereof is preferably 5 to 80 mass %, more preferably 30 to 70 mass %, based on 100 mass % of the urethane resin solid content. When the content of the structural unit derived from polyester polyol is within the above range, the oxygen barrier property and blocking resistance after bending are good.
[0102] In addition to the oil-based urethane resin, the oil-based anchor coat layer preferably further contains a co-used resin such as a vinyl chloride resin, a polyvinyl acetal resin, a cellulose resin, a polyamide resin, etc. The co-used resin is preferably a vinyl chloride resin and / or a polyvinyl acetal resin, and more preferably a vinyl chloride resin. The mass ratio of the oil-based urethane resin to the above-mentioned combined resin is preferably 3:7 to 9.9:0.1, more preferably 5:5 to 9.5:0.5, and further preferably 7:3 to 9:1.
[0103] The content of the oil-based urethane resin is preferably 20 to 90% by mass, more preferably 40 to 85% by mass, and even more preferably 60 to 80% by mass, based on the total mass of the anchor coat layer, in order to improve the oxygen barrier property after bending.
[0104] <Vinyl chloride resin> The vinyl chloride resin includes a structure obtained by polymerizing a monomer having an unsaturated double bond (excluding vinyl chloride monomer) and a vinyl chloride monomer. Suitable examples of the vinyl chloride resin include vinyl chloride-acrylic copolymer resin and vinyl chloride-vinyl acetate copolymer resin.
[0105] <Vinyl chloride-acrylic copolymer resin> The vinyl chloride-acrylic copolymer resin is mainly composed of a copolymer of vinyl chloride and an acrylic monomer, and the acrylic monomer is a monomer having an acrylic group or a methacrylic group, and preferably contains an acrylic monomer having a hydroxyl group. (Hereinafter, "acrylic or methacrylic" may be referred to as "(meth)acrylic.") The vinyl chloride-acrylic copolymer resin may be a block copolymer or random copolymer of vinyl chloride and an acrylic monomer, or a graft copolymer in which an acrylic monomer is grafted to the side chain of polyvinyl chloride.
[0106] The mass average molecular weight of the vinyl chloride-acrylic copolymer resin is preferably 10,000 to 100,000, and more preferably 30,000 to 70,000. The glass transition temperature of the vinyl chloride-acrylic copolymer resin is preferably 50 to 90°C, more preferably 55 to 85°C, and even more preferably 65 to 80°C. The hydroxyl value of the vinyl chloride-acrylic copolymer resin is preferably 10 to 120 mgKOH / g, more preferably 20 to 110 mgKOH / g, even more preferably 30 to 100 mgKOH / g, and particularly preferably 40 to 80 mgKOH / g. The content of the vinyl chloride-derived structure in the vinyl chloride-acrylic copolymer resin is preferably 70 to 95 mass% in 100 mass% of the solid content of the vinyl chloride-acrylic copolymer resin.
[0107] As the vinyl chloride-acrylic copolymer resin, for example, commercially available products such as Solvine A Type Series (manufactured by Shin-Etsu Chemical Co., Ltd.) can be used.
[0108] <Vinyl chloride-vinyl acetate copolymer resin> The vinyl chloride-vinyl acetate copolymer resin is a resin in which at least vinyl chloride and vinyl acetate are copolymerized, and the mass average molecular weight is preferably 5,000 to 100,000, and more preferably 20,000 to 70,000. In 100% by mass of the solid content of the vinyl chloride-vinyl acetate copolymer resin, the content of the structure derived from the vinyl acetate monomer is preferably 1 to 30% by mass, and the content of the structure derived from the vinyl chloride monomer is preferably 70 to 95% by mass. In addition, the vinyl chloride-vinyl acetate copolymer resin is more preferably one containing a hydroxyl group derived from vinyl alcohol derived from a saponification reaction or copolymerization, in order to improve the solubility in an organic solvent, and the hydroxyl value is preferably 20 to 200 mgKOH / g. In addition, the glass transition temperature of the vinyl chloride-vinyl acetate copolymer resin is preferably 50°C to 90°C.
[0109] As the vinyl chloride-acrylic copolymer resin, commercially available products such as Solvine C type series (manufactured by Shin-Etsu Chemical Co., Ltd.) can be used.
[0110] <Cellulose-based resin> Examples of the cellulose-based resin include nitrocellulose, cellulose acetate propionate, cellulose acetate butyrate, hydroxyalkylcellulose, and carboxyalkylcellulose. The alkyl group may be, for example, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, or a hexyl group, and the alkyl group may further have a substituent. Among these, cellulose acetate propionate, cellulose acetate butyrate, and nitrocellulose are preferred. The mass average molecular weight of the cellulose resin is preferably 5,000 to 1,000,000, and more preferably 10,000 to 200,000. The glass transition temperature of the cellulose-based resin is preferably 100°C to 160°C.
[0111] As the cellulose-based resin, commercially available products such as the CAB series (cellulose acetate butyrate resin manufactured by Eastman Co.) and the CAP series (cellulose acetate propionate resin manufactured by Eastman Co.) can be used.
[0112] <Polylactic acid resin> Polylactic acid resin is a biomass plastic whose main skeleton is polylactic acid produced through a chemical process using starch or sugar derived from plants as a raw material. Unlike conventional plastics made from petroleum, after use, it is placed in an environment with moderate moisture and temperature, such as in compost or soil, where hydrolysis is promoted, and then decomposition (biodegradation) by microorganisms progresses, and it is a biodegradable resin that is finally completely decomposed into CO2 and water. Industrially, it is a polyester resin synthesized from lactide, which is a cyclic dimer of lactic acid made from starch produced from corn, etc. Polylactic acid resin preferably contains 70 to 100% by mass, and more preferably 90 to 100% by mass, of structural units derived from polylactic acid relative to the entire polylactic acid resin. Polylactic acid resin can be obtained, for example, by the method described in JP 2023-037756 A.
[0113] <Resin contained in the water-based anchor coat layer> When the anchor coat layer is an aqueous anchor coat layer, it preferably contains an aqueous resin. The aqueous resin refers to a resin that is water-soluble or in an emulsion state. Suitable examples of the aqueous resin include a water-soluble resin and / or an emulsion resin, and a mixture thereof may also be used. Suitable examples of the aqueous resin include aqueous urethane resin, aqueous acrylic modified urethane resin, aqueous acrylic modified urethane urea resin, aqueous acrylic resin, aqueous styrene-acrylic acid copolymer resin, aqueous styrene-maleic acid copolymer resin, aqueous ethylene-acrylic acid copolymer resin, aqueous polyester resin, aqueous shellac, aqueous rosin modified maleic acid resin, aqueous vinyl chloride-vinyl acetate copolymer resin, aqueous vinyl chloride-acrylic acid copolymer resin, aqueous chlorinated polypropylene resin, aqueous hydroxyethyl cellulose resin, aqueous hydroxypropyl cellulose resin, aqueous butyral resin, etc. These resins can be used alone or in combination of two or more. Among them, the aqueous anchor coat layer preferably contains at least one aqueous resin selected from aqueous urethane resin, aqueous acrylic resin, aqueous styrene-acrylic acid copolymer resin, and aqueous styrene-maleic acid copolymer resin, and more preferably contains an aqueous urethane resin. The content of at least one aqueous resin selected from aqueous urethane resin, aqueous acrylic resin, aqueous styrene-acrylic acid copolymer resin, and aqueous styrene-maleic acid copolymer resin is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, and particularly preferably 80 to 99 mass% of the total mass of the resin contained in the aqueous anchor coat layer.
[0114] <Water-based urethane resin> From the viewpoint of improving the oxygen barrier property after bending, the aqueous anchor coat layer preferably contains an aqueous urethane resin. The aqueous urethane resin has an acid value that can be neutralized, and the acid value is preferably 20 to 65 mgKOH / g. The glass transition temperature of the aqueous urethane resin is preferably -30 to 0°C. Here, the glass transition temperature refers to the maximum value of Tan δ in dynamic viscoelasticity measurement. The hydroxyl value of the aqueous urethane resin is preferably 1 to 15 mgKOH / g. The preferred form of the number of urea bonds in the aqueous urethane resin is as described above in the explanation of <Urethane resin>.
[0115] The above-mentioned aqueous urethane resin can be obtained, for example, by the method described in JP-A-2008-001911, and is preferably in the form of a urethane resin synthesized from a polyol, a hydroxy acid, and a polyisocyanate, or a urethane resin containing a urethane prepolymer having an isocyanate group at its terminal, which is synthesized from a polyol, a hydroxy acid, and a polyisocyanate, and a polyurethane urea chain-extended with a polyamine.
[0116] [Print layer] The laminate of the present invention may have a printed layer. The printed layer preferably contains a resin and a colorant. The printed layer may be a layer that displays any design, pattern, character, symbol, etc. for the purpose of providing decoration or aesthetics; displaying the contents, expiration date, and manufacturer or seller, etc. The printed layer may be a solid printed layer having no design, pattern, letter, symbol, etc. The method for forming the printed layer is not particularly limited, and the printed layer may be formed, for example, using a printing ink. The printed layer may have a single layer structure or a multi-layer structure, and may be printed on the surface layer of the laminate. The mass per unit area of the printed layer is 0.1 to 12 g / m 2 It is preferable that the thickness is 0.5 to 6 g / m 2 More preferably, it is 1 to 3 g / m 2 It is more preferable that:
[0117] <Formation of printing layer> The printing layer can be formed, for example, by printing on a substrate using a printing ink and then removing the volatile components. The printing method is preferably a gravure printing method or a flexographic printing method, and, for example, the ink is diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing, and is supplied to each printing unit alone or in a mixture and applied. The printing layer can then be obtained by fixing the coating by drying in an oven or the like.
[0118] [Adhesive layer] The laminate of the present invention may contain an adhesive layer for the purpose of adhering each layer. The components of the adhesive layer are not particularly limited, and suitable examples include dry lamination adhesives such as olefin adhesives, acrylic adhesives, ethylene-vinyl acetate copolymer adhesives, reactive urethane adhesives, non-solvent lamination adhesives, imine anchor coating agents, butadiene anchor coating agents, isocyanate anchor coating agents, and thermoplastic resins used in extrusion lamination. The adhesive layer is preferably a reaction product of a reactive urethane adhesive consisting of polyisocyanate and polyol.
[0119] The method for bonding (also referred to as laminating) each layer with an adhesive layer is not particularly limited, and examples thereof include conventionally known methods such as extrusion lamination, dry lamination, and non-solvent lamination.
[0120] [Intermediate substrate] The laminate of the present invention may have an intermediate substrate for the purpose of improving rigidity. A specific example of the intermediate substrate is preferably a plastic substrate mainly containing polyolefin resin as a raw material, similar to the above-mentioned substrate. Examples of the intermediate substrate include polyolefin resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene-vinyl acetate copolymer, propylene homopolymer, and ethylene-propylene copolymer. The intermediate substrate may also be a composite substrate produced by a co-extrusion method. Furthermore, it is more preferable that the intermediate substrate is made of the same (same) material as the substrate and / or the sealant that is provided as necessary. Examples of the same (same) material include a combination of polypropylenes and polyethylenes.
[0121] [Sealant] It is also preferable that the laminate of the present invention further comprises a sealant. When the laminate is used as a packaging material, the inner layer of the sealant comes into direct contact with the packaged item, and serves to protect the packaged item. In order to make the laminate into a bag shape, the sealant is preferably a heat seal layer having heat sealability.
[0122] Examples of materials constituting the sealant include polyolefin resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene-vinyl acetate copolymer, acrylic resin, propylene homopolymer, and ethylene-propylene copolymer, and one or more of these resins can be used. The sealant may be composed of a single layer or may be composed of two or more layers. The sealant is preferably a non-stretched film or coating layer made of the above-mentioned resin, more preferably a coating layer. The coating layer can be formed, for example, by printing a coating agent such as a heat seal agent on a substrate, and then drying to remove volatile components.
[0123] <Heat seal layer> The heat seal layer is a layer having heat sealability, and is preferably formed from a heat seal agent. Specifically, for example, the heat seal layer can be formed by printing on a substrate using the heat seal agent, and then drying to remove volatile components. <Heat sealant> The heat-sealing agent preferably contains one or more selected from the group consisting of polyethylene resin, ethylene-vinyl acetate copolymer resin, and acrylic resin, and further contains a solvent. In addition, it may contain any additives such as a defoamer, an emulsifier, a preservative, a plasticizer, an amide wax, a hydrocarbon wax, and a chelating crosslinking agent. From the viewpoint of environmental load, the heat-sealing agent is preferably water-based.
[0124] [Packaging material] The laminate of the present invention can be suitably used to form packaging materials such as flexible packaging packages and packaging bags. The laminate of the present invention may be used alone as a packaging material, or may be used in combination with other materials. The packaging material may be a packaging container.
[0125] [Method of manufacturing laminate] The method for producing a laminate of the present invention is a method for producing a laminate having a substrate, a first barrier layer, and a second barrier layer, and includes a step of applying a first barrier coating agent to form a first barrier layer, and a step of applying a second barrier coating agent to form a second barrier layer, the first barrier coating agent including a hydrophilic resin, and the second barrier coating agent including a thermoplastic styrene elastomer and a hydrocarbon wax. It is preferable that the method for producing a laminate of the present invention further includes a step of applying an anchor coating agent onto the substrate to form an anchor coating layer. It is also preferable that the method for producing a laminate of the present invention further includes a step of applying a heat seal agent to form a heat seal layer. EXAMPLES
[0126] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted.
[0127] <Hydroxyl value> The hydroxyl value is the number of milligrams of potassium hydroxide required to neutralize acetic acid bonded to hydroxyl groups when 1 g of a sample is acetylated, and was measured by the method described in JIS K 0070.
[0128] <Acid value> The acid value is the number of milligrams of potassium hydroxide required to neutralize the free fatty acids, resin acids, etc. contained in 1 g of a sample, and was measured by the method described in JIS K 0070.
[0129] <Amine value> The amine value is the amount of potassium hydroxide in mg equivalent to the amount of hydrochloric acid required to neutralize the amino groups contained in 1 g of sample, and was measured in accordance with JIS K 0070. 0.5 to 2 g of sample was precisely weighed out (sample solid content: Sg), and 50 mL of a mixed solution of methanol / methyl ethyl ketone = 60 / 40 (mass ratio) was added to the precisely weighed sample to dissolve it. Bromophenol blue was added as an indicator to the resulting solution, and the resulting solution was titrated with a 0.2 mol / L ethanolic hydrochloric acid solution (titer: f). The point at which the color of the solution changed from green to yellow was set as the end point, and the titration amount (AmL) at this time was used to calculate the amine value according to the following (Equation 11). (Formula 11) Amine value = (A x f x 0.2 x 56.108) / S [mgKOH / g]
[0130] <Mass average molecular weight> The weight average molecular weight was determined by measuring the molecular weight distribution using a gel permeation chromatography (GPC) device (HLC-8220 manufactured by Tosoh Corporation) and calculating the molecular weight converted using polystyrene as a standard substance. The measurement conditions are shown below. Columns: The following columns were used in series connection: Tosoh Corporation TSKgel Super AW2500 Tosoh Corporation TSKgel Super AW3000 Tosoh Corporation TSKgel Super AW4000 Tosoh Corporation's TSK gelguard column Super AWH Detector: RI (differential refractometer) Measurement conditions: Column temperature 40℃ Eluent: Tetrahydrofuran Flow rate: 1.0mL / min
[0131] <Glass transition temperature (Tg)> The glass transition temperature was determined by differential scanning calorimetry (DSC). The measurement was performed using a Rigaku DSC8231 under conditions of a measurement temperature range of -70 to 250°C and a heating rate of 10°C / min. The midpoint (inflection point) of the baseline shift based on the glass transition in the obtained DSC curve was taken as the glass transition temperature.
[0132] Details of the abbreviations for the polyvinyl alcohol resin PVA, inorganic layered filler X, thermoplastic styrene elastomer TPS, and styrene butadiene latex SBR described in the examples are shown below.
[0133] <Polyvinyl alcohol resin PVA> PVA1: Kuraray Co., Ltd. Product name: Exeval AQ-4104 (ethylene vinyl alcohol resin, ethylene content: 8 mol%, solid mass% = 100%) PVA2: Kuraray Co., Ltd., Kuraray Poval 28-98, polyvinyl alcohol, solid content by mass % = 100% PVA3: Sekisui Chemical Co., Ltd., ULTILOC5003, amine-modified polyvinyl alcohol, solid content by mass % = 100%
[0134] <Inorganic layered filler X> X1: Montmorillonite (swelling, average particle size: 2 μm, aspect ratio: 500, specific surface area: 13.1 m 2 / g, particle thickness: 1 nm, average major axis: 500 nm, solid content 100%) X2: Mica (average particle size: 6 μm, aspect ratio: 100, specific surface area: 9 m 2 / g, solid content 100%) X3: Kaolin (average particle size 1.2 μm, aspect ratio 100, specific surface area 10 m 2 / g, solid content 100%)
[0135] <Thermoplastic styrene elastomer TPS> TPS1: Kaneka Corporation Product name: SIBSTAR 073T (styrene-isobutylene-styrene block copolymer, solid content 100%) TPS2: Kraton Corporation Product name: G1650 (styrene-ethylene-butylene-styrene block copolymer, solids content 100%) TPS3: Kraton Corporation Product name: FG1924 (maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer, solids content 100%)
[0136] <Styrene butadiene latex SBR> SBR1: Zeon Corporation, product name: Nipol SX1105 (styrene butadiene latex, solids content 45%)
[0137] <Hydrocarbon wax> WAX1: Nippon Seiro Co., Ltd. Product name: Paraffin Wax 135 (Paraffin wax, melting point: 59°C, linear structure component content: 92% or more, solid content 100%) WAX2: Chukyo Yushi Co., Ltd. Product name: M-300 (paraffin wax emulsion, 50% solids, solvent: water)
[0138] (Manufacturing of barrier coating agents) <Production Example 1> First Barrier Coating Agent A1 6 parts of polyvinyl alcohol resin PVA1 and 92 parts of mixed solvent (water / IPA=8 / 2) were mixed and heated with stirring, and the mixture was heated and stirred at 95°C for 1 hour, after which the heating was stopped and stirring was continued until the mixture returned to room temperature, to obtain an aqueous solution of polyvinyl alcohol resin PVA1. 2 parts of inorganic layered filler X1 were added to the aqueous solution of polyvinyl alcohol resin PVA1, and the mixture was stirred to obtain a first barrier coating agent A1.
[0139] <Production Examples 2 to 6> First Barrier Coating Agents A2 to A6 First barrier coating agents A2 to A6 were obtained in the same manner as in Production Example 1, except that the raw materials and compounding ratios were changed to those shown in Table 1.
[0140] [Table 1]
[0141] <Production Example 7> Second Barrier Coating Agent B1 20 parts of thermoplastic styrene elastomer TPS1, 10 parts of hydrocarbon wax WAX1, and 68 parts of solvent MCH (methylcyclohexane) (δd: 16.0, δp: 0) were mixed and heated with stirring, and the mixture was heated and stirred at 80°C for 1 hour. After that, the mixture was stopped and stirred until it returned to room temperature, to obtain a thermoplastic styrene elastomer TPS1 solution. 2 parts of amorphous silica (Mizusawa Chemical Industry Co., Ltd., Mizukasil P707, average particle size (laser scattering method): 4 μm, oil absorption: 250 ml / 100 g, solid mass% = 100%) were added to the thermoplastic styrene elastomer TPS1 solution, and the mixture was stirred to obtain a second barrier coating agent B1.
[0142] <Production Examples 8 to 12, Comparative Production Example 2> Second Barrier Coating Agent B2 to 6, 8 Second barrier coating agents B2 to B6 and B8 were obtained in the same manner as in Production Example 7, except that the raw materials and compounding ratios were changed to those shown in Table 2.
[0143] Comparative Example 1: Second barrier coating agent B7 A second barrier coating agent B7 was obtained by mixing and stirring 44.4 parts of styrene butadiene latex SBR1, 20 parts of hydrocarbon wax 2, and 33.6 parts of water.
[0144] [Table 2]
[0145] (Resin synthesis) <Synthesis Example 1> Urethane resin PU1 120.6 parts of ethyl acetate, 153.7 parts of polyester polyol having a number average molecular weight of 2,000, which is a condensation product of 3-methyl-1,5-pentanediol and adipic acid, 27.9 parts of polyester polyol having a number average molecular weight of 5,000, which is a condensation product of 3-methyl-1,5-pentanediol and adipic acid, 12.4 parts of polypropylene glycol having a number average molecular weight of 700, 35.0 parts of polypropylene glycol having a number average molecular weight of 2000, and 52.3 parts of isophorone diisocyanate were mixed and reacted in a nitrogen atmosphere at 90°C for 5 hours to obtain a urethane prepolymer having an isocyanate terminal. Next, 279.6 parts of isopropanol, 299.7 parts of ethyl acetate, 2.1 parts of iminobispropylamine, and 16.6 parts of isophoronediamine were mixed with stirring, and the obtained urethane prepolymer with a terminal isocyanate was gradually added at 40° C. The mixture was reacted at 80° C. for 1 hour to obtain a solution of urethane resin PU1 having a solid content of 30% by mass, a urea bond concentration of 0.78 mmol / g, an amine value of 1.3 mgKOH / g, and a mass average molecular weight of 36,100.
[0146] <Synthesis Example 2> Urethane resin PU2 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube was charged with 24.3 parts of a polyester polyol having a number average molecular weight of 2,000 obtained by condensation polymerization of biomass sebacic acid / adipic acid = 50 / 50 (mass ratio) and 1,3-propanediol / neopentyl glycol = 50 / 50 (mass ratio), 4 parts of isophorone diisocyanate, and 10 parts of ethyl acetate, and reacted for 6 hours at 120 ° C. under a nitrogen atmosphere, added with 14 parts of propyl acetate, and cooled to obtain a solution of a urethane prepolymer with a terminal isocyanate. Next, the obtained solution of urethane prepolymer having an isocyanate terminal was gradually added at room temperature to a mixture of 1.7 parts of isophoronediamine, 18 parts of ethyl acetate, and 28 parts of isopropyl alcohol, and then the mixture was allowed to react at 50°C for 1 hour to obtain a urethane resin solution PU2 having a solid content of 30%, a urea bond concentration of 0.78 mmol / g, a mass average molecular weight of 70,000, and an amine value of 5 mg KOH / g.
[0147] <Synthesis Example 3> Polylactic acid resin PLA1 A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube was charged with 100 parts of D,L-lactide and 0.1 parts of octanol and heated. After reaching 180°C, 0.05 parts of tin 2-ethylhexanoate was added and ring-opening polymerization was carried out for 2 hours. After that, 0.08 parts of 116% strong phosphoric acid was added and the residual lactide was removed under reduced pressure. The solid content was adjusted to 50% with ethyl acetate to obtain a polylactic acid resin solution PLA1 having a mass average molecular weight of 50,000.
[0148] (Manufacturing of anchor coating agents) <Production Example 13> Anchor Coating Agent AC1 47 parts of urethane resin PU1 solution, 15 parts of vinyl chloride-vinyl acetate resin PVC1 solution (hydroxyl value: 154 mg KOH / g, mass average molecular weight: 28,000, glass transition temperature: 78 ° C., solid content 25%), 1 part of amorphous silica (Mizusawa Chemical Industry Co., Ltd., Mizukasil P-707, average particle size (laser scattering method): 4 μm, oil absorption: 250 ml / 100 g, solid content 100%), 1 part of chlorinated polypropylene solution (Nippon Paper Industries Co., Ltd., Super Chron 390S, solid content = 50%), 0.5 parts of fatty acid amide solution (lauric acid amide, solid content 50%), 30.5 parts of mixed solvent (normal propyl acetate (NPAC) / isopropyl alcohol (IPA) = 7 / 3 (mass ratio)), 3 parts of propylene glycol monomethyl ether, and 2 parts of water were mixed and dispersed for 20 minutes with a bead mill to obtain a pigment dispersion. The resulting pigment dispersion was mixed with 2 parts of water with stirring to obtain anchor coating agent AC1.
[0149] <Production Example 14> Anchor Coating Agent AC2 20 parts of urethane resin PU2 solution, 10 parts of vinyl chloride-vinyl acetate resin solution, silica particles (average particle size 5 μm, BET specific surface area 200 m 2Anchor coating agent AC2 was obtained by stirring and mixing 1 part of urethane resin solution (1.2 parts / g) and 26 parts of a mixed solvent (NPAC / IPA = 7 / 3 (mass ratio)) and grinding in a sand mill. Then, 20 parts of the urethane resin solution, 19.7 parts of the mixed solvent (NPAC / IPA = 7 / 3 (mass ratio)), 0.1 part of polyalkyl vinyl ether (polyvinyl butyl ether copolymer, number average molecular weight 5,000, solids content 20%), 3.0 parts of water, and 0.2 parts of a quaternary ammonium salt (lauryl trimethyl ammonium chloride, solids content 50%) were obtained by stirring and mixing.
[0150] <Production Example 15> Anchor Coating Agent AC3 Anchor coating agent AC3 was obtained by mixing and stirring 33.3 parts of nitrocellulose (nitrogen content 11.5% or more and 12.2% or less, mass average molecular weight 28,000 to 33,000, solid content 30%), 39.9 parts of ethyl acetate, 20.0 parts of polylactic acid resin solution PLA1 (solid content 50%), 0.9 parts of Orgatix TC-100 (titanium chelate manufactured by Matsumoto Fine Chemical Co., Ltd., solid content 75%), 2.0 parts of diethylene glycol monobutyl ether, and 3.9 parts of Sunwax 131P (polyethylene wax, solid content 40%).
[0151] <Production Example 16> Heat sealant HS1 91.7 parts of acrylic resin emulsion AC1 (JONCRYL PDX7356 manufactured by BASF, acid value: 78 mgKOH / g, glass transition temperature: 25°C, solid content: 50%), 8.2 parts of a water / isopropyl alcohol mixed solvent (mass ratio 1:1), and 0.1 part of BYK-024 (antifoaming agent manufactured by BYK) were mixed with stirring to obtain a heat sealing agent HS1.
[0152] <Production Example 17> Heat sealant HS2 A heat sealing agent HS2 was obtained by mixing and stirring 91.7 parts of polyethylene resin emulsion PE1 (manufactured by Mitsui Chemicals, Inc., Chemipearl S500, ionomer resin, solid content: 50%), 8.2 parts of a water / isopropyl alcohol mixed solvent (mass ratio 1:1), and 0.1 part of BYK-024 (manufactured by BYK, defoamer).
[0153] <Production Example 18> Heat sealant HS3 91.7 parts of ethylene-vinyl acetate copolymer resin emulsion EVA1 (Sumitomo Chemical Co., Ltd., Sumikaflex S-400HQ, minimum film-forming temperature: 0°C, glass transition temperature: 0°C, vinyl alcohol resin emulsifier, solid content: 50%), 8.2 parts of a water / isopropyl alcohol mixed solvent (mass ratio 1:1), and 0.1 part of BYK-024 (BYK, defoamer) were mixed and stirred to obtain a heat sealing agent HS3.
[0154] (Manufacture of laminates) Example 1: Laminate P1 100 parts of the first barrier coating agent A1 was diluted with a mixed solvent (isopropyl alcohol / water) to a Zahn cup #3 (Rigo Co., Ltd.) of 16 seconds (25°C). Similarly, 100 parts of the second barrier coating agent B1 was diluted with MCH (methylcyclohexane) to a Zahn cup #3 (Rigo Co., Ltd.) of 17 seconds (25°C), and 100 parts of the anchor coating agent AC1 was diluted with a mixed solvent (isopropyl alcohol / ethyl acetate) to a Zahn cup #3 (Rigo Co., Ltd.) of 15 seconds (25°C), and then 3 parts of the curing agent H1 (Duranate P-301-75E, Asahi Kasei Co., Ltd., hexamethylene diisocyanate-based curing agent, adduct type, NV.50%) was added and mixed and stirred. Then, the entire surface of the corona-treated surface of the corona-treated biaxially oriented polypropylene (OPP) film (thickness 20 μm) was printed with the anchor coating agent AC1 diluted and containing the curing agent H1 at a printing speed of 50 m / min and an in-line oven temperature of 60° C. using a gravure printing machine equipped with a gravure plate having a plate depth of 30 μm to form an anchor coating layer. The diluted barrier coating agent A1 was printed twice on the anchor coating layer at a printing speed of 50 m / min and an in-line oven temperature of 60° C. using a gravure printing machine equipped with a gravure plate having a plate depth of 30 μm to form a first barrier layer. Then, the diluted second barrier coating agent B1 was printed three times using a gravure printing machine equipped with a gravure plate having a plate depth of 60 μm to form a second barrier layer, thereby obtaining a laminate P1 having a configuration of OPP (substrate) / anchor coating layer / first barrier layer / second barrier layer. The mass per unit area of the anchor coating layer of the laminate P1 was 0.4 g / m2 , the mass per unit area of the first barrier layer is 1.0 g / m 2 , the mass per unit area of the second barrier layer is 10.0 g / m 2 It was.
[0155] <Examples 2 to 23 and Comparative Examples 1 to 4> Laminates P2 to 27 Laminates P2 to P27 were obtained in the same manner as in Example 1, except that the first barrier coating agent, the second barrier coating agent, the anchor coating agent, the heat sealing agent, and the laminate structure were changed so as to obtain the laminate structures shown in Tables 3 and 4. The coating method for the heat sealing agent was as follows. Heat sealant dilution: None Printing equipment: Gravure printing machine with a gravure plate with a plate depth of 50 μm Printing conditions: Printing speed 50m / min, in-line oven 70℃, printing over 2 times
[0156] <Examples 24 to 46> Laminates P28 to P50 Laminates P28 to 50 were obtained in the same manner as in Example 1, except that the type of the first barrier coating agent and its mass per unit area, the second barrier coating agent, the anchor coating agent, the heat sealing agent, and the lamination structure were changed so as to obtain the laminate structure shown in Table 5. The type of paper substrate, the mass per unit area of the first barrier coating agent, and the coating method of the heat sealing agent are as follows. Paper base material: Daio Paper Co., Ltd. Product name: Nagoya Sarashi Ryuo (single-sided gloss paper, weight 70 g / m 2 ) Mass per unit area of first barrier coating agent: 3g / m 2 Heat sealant dilution: None Printing equipment: Gravure printing machine with a gravure plate with a plate depth of 50 μm Printing conditions: Printing speed 50m / min, in-line oven 70℃, printing over 2 times
[0157] <Evaluation of oxygen barrier properties of laminate before bending> The obtained laminate was cut into 100 mm squares, and the oxygen permeability was measured by a method conforming to JIS K 7126-2:2006. The measurement conditions were high humidity conditions of 23°C and 90% RH, and the surface of the laminate having the second barrier layer was set in an oxygen permeability measuring device OX-TRAN (manufactured by MOCON) with the surface facing the humidity-controlled side, and the oxygen permeability was measured. For the laminate of Comparative Example 2 not having a second barrier layer, the measurement was performed with the first barrier layer facing the humidity-controlled side. Note that A, B, and C are ranges that are practically acceptable. Evaluation Criteria A (Excellent): Oxygen permeability is 10g / m 2 Less than 24 hours. B (Good): Oxygen permeability is 10g / m 2 ·Over 24 hours, 100g / m 2 Less than 24 hours. C (Acceptable): Oxygen permeability is 100g / m 2 ·24h or more, 200g / m 2 Less than 24 hours. D (Not acceptable): Oxygen permeability is 200g / m 2 -24 hours or more.
[0158] <Oxygen barrier properties after bending> The obtained laminate was cut into a 100 mm square, folded so that the same faces of the laminate overlapped each other, and a pressure of 1 kg / m was applied to the folded part. 2 A load was applied for 5 seconds. The folded portion was cut into 3 mm squares, and the oxygen permeability was measured by a method conforming to JIS K 7126-2:2006. The measurement conditions were normal conditions of 23°C and 65% RH, and the surface of the laminate having the second barrier layer was set in an oxygen permeability measuring device OX-TRAN (manufactured by MOCON) with the surface facing the humidity-controlled side, and the oxygen permeability was measured. For the laminate of Comparative Example 2 not having a second barrier layer, the measurement was performed with the first barrier layer facing the humidity-controlled side. Note that A, B, and C are ranges that do not cause any practical problems. Evaluation Criteria A (Excellent): Oxygen permeability is 10g / m 2 Less than 24 hours. B (Good): Oxygen permeability is 10g / m 2 ·Over 24 hours, 100g / m 2Less than 24 hours. C (Acceptable): Oxygen permeability is 100g / m 2 ·24h or more, 200g / m 2 Less than 24 hours. D (Not acceptable): Oxygen permeability is 200g / m 2 -24 hours or more.
[0159] <Blocking resistance> The obtained laminate was cut into two pieces of 40 mm square, and the substrate surface of one laminate piece was completely overlapped with the second barrier layer surface of the other laminate piece, and the laminate was then subjected to a temperature of 40°C, a humidity of 80% RH, and a load of 100 N / cm 2 The laminate was pressed under the environment of 100° C. In Examples 15 to 19, in which the substrate surface was not exposed, the first barrier layer surface and the second barrier layer surface were completely overlapped, and in Examples 21 to 23, the second barrier layer and the heat seal layer were completely overlapped, and then the above-mentioned pressing operation was performed. After leaving the laminate for 24 hours, the two overlapping laminates were peeled off from each other, and the state of transfer of the barrier layer to the other surface was visually observed and evaluated according to the following criteria. A, B, and C are ranges that do not cause any problems in practical use. Evaluation Criteria A (Excellent): The amount of transfer of the barrier layer is less than 5% by area. B (Good): The amount of transfer of the barrier layer is 5% or more and less than 10% by area. C (Acceptable): The amount of transfer of the barrier layer is 10% or more by area and less than 25% by area. D (Fail): The amount of transfer of the barrier layer is 25% or more and less than 50% by area. E (unacceptable): The amount of transfer in the barrier layer is 50% or more by area.
[0160] [Table 3]
[0161] [Table 3]
[0162] [Table 4]
[0163] [Table 5]
[0164] [Table 5]
[0165] As the above evaluation results show, Comparative Example 1 did not have a first barrier layer, and therefore was poor in terms of oxygen barrier property at a humidity of 90% and blocking resistance. Comparative Example 1 did not have a second barrier layer, and therefore was poor in terms of oxygen barrier property at a humidity of 90% and oxygen barrier property after folding. Comparative Example 3 did not have a second barrier layer containing no hydrocarbon wax, and therefore was poor in terms of oxygen barrier property and blocking resistance at a humidity of 90%. Comparative Example 4 did not have a thermoplastic styrene elastomer, and therefore was poor in terms of oxygen barrier property at a humidity of 90%. On the other hand, in the Examples, since the first barrier layer contains a hydrophilic resin and the second barrier layer contains a thermoplastic styrene elastomer resin and a hydrocarbon-based wax, it was confirmed that the examples exhibit high oxygen barrier property not only under normal humidity conditions but also under high humidity conditions, and furthermore, that the examples exhibit high oxygen barrier property even after a bending test, and further confirmed that a laminate with high blocking resistance can be formed.
Claims
1. A laminate having a substrate, a first barrier layer, and a second barrier layer, the first barrier layer comprises a hydrophilic resin, The laminate, wherein the second barrier layer comprises a thermoplastic styrene elastomer and a hydrocarbon-based wax.
2. 2. The laminate according to claim 1, wherein the thermoplastic styrene elastomer is a styrene-based block copolymer.
3. The laminate according to claim 2, wherein the styrene-based block copolymer is at least one selected from the group consisting of styrene-isoprene-styrene block copolymer (SIS), styrene-isobutylene-styrene block copolymer (SIBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butylene-styrene block copolymer (SBS), styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-isoprene-styrene block copolymer (SBIS), hydrogenated styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), and styrene-butadiene block copolymer (SB), as well as acid-modified, acid anhydride-modified, and amine-modified products thereof.
4. 3. The laminate according to claim 1, wherein the mass ratio of the thermoplastic styrene elastomer to the hydrocarbon wax in the second barrier layer is from 95:5 to 30:
70.
5. The laminate of claim 1 or 2, wherein the first barrier layer further comprises an inorganic layered filler.
6. 6. The laminate according to claim 5, wherein the inorganic layered filler is at least one selected from the group consisting of montmorillonite, mica, and kaolin.
7. 3. The laminate of claim 1 or 2, wherein the second barrier layer further comprises an extender pigment.
8. The laminate according to claim 1 or 2, wherein the substrate is a plastic substrate or a paper substrate.
9. The laminate according to claim 1 or 2, further comprising an anchor coat layer.
10. The laminate of claim 1 or 2, further comprising a sealant.
11. A method for producing a laminate having a substrate, a first barrier layer, and a second barrier layer, comprising the steps of: A step of applying a first barrier coating agent to form a first barrier layer; applying a second barrier coating agent to form a second barrier layer; the first barrier coating agent contains a hydrophilic resin, The method for producing a laminate, wherein the second barrier coating agent comprises a thermoplastic styrene elastomer and a hydrocarbon wax.
Citation Information
Patent Citations
Resin composition for moisture-proofing treatment and moisture-proofing material
JP2001254296A
Gas barrier laminate and its manufacturing method
JP2005144761A
Liner for cap, cap, and bottle having cap
JP2008174249A
Barrier material
JP2020157757A
Gas barrier film
JP2021194822A